2001
DOI: 10.1520/jfs15171j
|View full text |Cite
|
Sign up to set email alerts
|

How Many Samples from a Drug Seizure Need to Be Analyzed?

Abstract: Recently Aitken (1) introduced an outstanding advance in the approach to decision making regarding drugs sampling. Unfortunately this approach has not, as yet, been widely implemented despite being based on a solid mathematical foundation. In this paper we advocate a Bayesian approach along the lines of that outlined by Aitken but designed to be both easily understood with less mathematical sophistication and implementable using standard EXCEL® software. The emphasis is placed on encouraging the application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…The utility of a Bayesian approach in forensic science, including ballistic (Bunch, 2000) and paint matching (McDermott et al, 1999), drug sampling and analysis (Coulson et al, 2001;Goldmann et al, 2004), and DNA identification (Krawczak and Schmidtke, 1992;Evett and Weir, 1998;Thompson et al, 2003;Foreman et al, 1999), is widely known, as it provides the examiner with the likelihood ratio of a positive identification or match that can be presented in court.…”
Section: Osteological Data Likelihood Ratios and Personal Identificmentioning
confidence: 99%
“…The utility of a Bayesian approach in forensic science, including ballistic (Bunch, 2000) and paint matching (McDermott et al, 1999), drug sampling and analysis (Coulson et al, 2001;Goldmann et al, 2004), and DNA identification (Krawczak and Schmidtke, 1992;Evett and Weir, 1998;Thompson et al, 2003;Foreman et al, 1999), is widely known, as it provides the examiner with the likelihood ratio of a positive identification or match that can be presented in court.…”
Section: Osteological Data Likelihood Ratios and Personal Identificmentioning
confidence: 99%
“…It is reasonable to expect that underestimation (a false positive) could occur with a frequency defined by the significance level selected both for the CI of the mean weight and identity estimation. 4. Has the sampling method saved significant time and labor over the approach of weighing and chemically identifying every item needed to meet a threshold amount?…”
Section: Validation Of Sampling Methodsmentioning
confidence: 99%
“…Variations of the sampling approach and related issues in the context of seized-drug analysis have been described in journal articles and texts [1][2][3][4][5][6][7][8][9][10][11][12]. International standardizing bodies have published helpful terminologies and protocols on the subjects of sampling and statistics in general [13,14] and on seized-drug sampling in particular [14].…”
Section: Introductionmentioning
confidence: 99%
“…During re-sampling, it is essential that the following principles are maintained: the properties of the sample are a true reflection of the properties of the population from which the samples were taken; and, each unit in the population has an equal chance of being selected [13] [14] [19]. For simplicity, after having observed that the external characteristics are the same, all the units can be put in a "black box" like a plastic bag, and a sample can be chosen randomly.…”
Section: Literature Reviewmentioning
confidence: 99%